A new species of Sunipea Griffin & Tranter, 1986 (Crustacea: Brachyura: Inachidae) and a redescription of Sunipea indicus (Alcock, 1895) - Santana, William (Zootaxa, 2015)
A new species of spider crab, Sunipea callistus, n. sp., from Cape Guardafui, Somali Republic, is described and illustrated. Sunipea indicus (Alcock, 1895) is also redescribed and figured. Sunipea callistus n. sp. differs from S. indicus in the structures of the carapace, third maxillipeds, thoracic sternum, male abdomen, and chelipeds. Despite a number of characteristics that separate both species, these differences are more pronounced in males and are less evident in females. A diagnosis for the genus is provided.